Pengaruh Pengunaan Media Pembelajaran Power Point Dan Scratch Pada Mata Pelajaran Informatika Materi Sistem Komputer - Hafif Assulamy; Haratua Tiur Maria S; Venny Karolina (Departement of Mathematics Education, 2023)
This research aims to evaluate the influence of the use of instructional media, specifically PowerPoint and Scratch, on the learning outcomes of seventh-grade students at MTS Islamiyah Pontianak in the subject of Informatics with Computer System material. Using an experimental method and data analysis through SPSS, the results of the study indicate that there is no significant difference in learning outcomes between the group using PowerPoint and the group using Scratch as instructional media. This finding holds important implications for the development of instructional media in the context of Informatics education, demonstrating that both media options have an equal impact on enhancing students' understanding of Computer System material. These findings provide valuable guidance for the development of more effective and engaging teaching strategies in the digital education era.